Monitoring respiratory mechanics as a training tool for manual ventilation - Carlomagno, Carlos Eduardo Baldo; Mascaretti, Renata Suman; Lyra, João Cesar; Zacharias, Romy Schmidt Brock; Magalhaes, Mauricio; Breuel, Pedro Alexandre Federico; Rebello, Celso Moura (Frontiers in Pediatrics, 2025)
IntroductionApproximately 500,000 newborns in Brazil require respiratory support at birth each year. Manual ventilation is essential in neonatal resuscitation, but achieving adequate tidal volume (Tv) delivery and minimizing face mask leakage remain challenging. Respiratory Function Monitors (RFMs) offer real-time feedback that may enhance training effectiveness. This study aimed to assess the impact of RFM use on improving manual ventilation skills among neonatology residents using self-inflating bags (SIB) and T-piece resuscitators, focusing on optimizing Tv delivery and reducing mask leakage.MethodsA prospective experimental study was conducted with 23 neonatology residents from four training programs. Participants performed manual ventilation on a neonatal manikin across five sessions: baseline without RFM (V1), with RFM feedback (V2), immediately post-training without RFM (V3), and follow-ups at one month (V4) and three months (V5) without RFM. Tidal volume and mask leakage were recorded using a computerized acquisition system. Data were analyzed using mixed linear models for repeated measures.ResultsThe participants had a mean age of 29 years; 91.3% were female, and 60.9% were first-year residents. At baseline, SIB ventilation resulted in excessive Tv [mean: 10.43 ml/kg (95% CI: 9.15–11.72)]. Following RFM-based training, Tv decreased significantly and remained within lung-protective limits (4–6 ml/kg) across all subsequent sessions (p < 0.001). However, mask leakage consistently exceeded the 20% threshold, regardless of device or session.DiscussionRFM-based training significantly improved tidal volume control, supporting the adoption of lung-protective ventilation techniques among neonatology residents. Despite these gains, high levels of mask leakage persisted, suggesting the need for targeted instruction in mask handling and sealing. The retention of improved ventilation performance over three months highlights the educational value of RFM in neonatal resuscitation training.